2015
DOI: 10.3758/s13428-015-0686-9
|View full text |Cite
|
Sign up to set email alerts
|

Using Automated Learning Devices for Monkeys (ALDM) to study social networks

Abstract: Social network analysis has become a prominent tool to study animal social life, and there is an increasing need to develop new systems to collect social information automatically, systematically, and reliably. Here we explore the use of a freely accessible Automated Learning Device for Monkeys (ALDM) to collect such social information on a group of 22 captive baboons (Papio papio). We compared the social network obtained from the co-presence of the baboons in ten ALDM testing booths to the social network obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 21 publications
2
37
0
Order By: Relevance
“…Recent studies have demonstrated that monkeys can be trained to perform complex tasks using touchscreen devices that can be easily integrated into a naturalistic environment (Rumbaugh et al, 1989;Mandell and Sackett, 2008;Fagot and Paleressompoulle, 2009;Gazes et al, 2013;Calapai et al, 2017;Claidière et al, 2017;Tulip et al, 2017;Berger et al, 2018). Finally, it should be possible to obtain stable gaze signals from unrestrained animals.…”
Section: Recording Brain Activity During Natural and Complex Behaviormentioning
confidence: 99%
“…Recent studies have demonstrated that monkeys can be trained to perform complex tasks using touchscreen devices that can be easily integrated into a naturalistic environment (Rumbaugh et al, 1989;Mandell and Sackett, 2008;Fagot and Paleressompoulle, 2009;Gazes et al, 2013;Calapai et al, 2017;Claidière et al, 2017;Tulip et al, 2017;Berger et al, 2018). Finally, it should be possible to obtain stable gaze signals from unrestrained animals.…”
Section: Recording Brain Activity During Natural and Complex Behaviormentioning
confidence: 99%
“…The links in bold are the ones present in both top ten rankings. aggregation window of one month is usually advocated [22,48]. In the case of data 360 collected through wearable sensors on the other hand, a large amount of contacts is 361 already recorded after a few hours.…”
Section: Rank Interaction Network (Observations) Contacts Network (Sementioning
confidence: 99%
“…Comparison between 70 sensors and direct observations or videos have yielded mixed results [46,47]. Among 71 animals, different types of networks built from the same data set of direct observations 72 have been shown to differ [41,42], while a social network deduced from co-presence in 73 cognitive testing booths has been shown to correlate with the one obtained from 74 directly observed interactions [48,49]. However, we are not aware of studies using data 75 collected in the same population with on the one hand wearable sensors and on the 76 other hand direct observations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For our study, we decided to focus solely on grooming as it is known to be a bonding activity in primates and therefore to represent affiliative relationships accurately (Seyfarth, 1977). More details on the behavioural observations can be found in (Claidière et al, 2017).…”
Section: Behavioural Datamentioning
confidence: 99%